Pemanfaatan Internet Terhadap Kinerja Penyuluh Pertanian Padi Sawah Di Kecamatan Angata Kabupaten Konawe Selatan - Lalu Muhammad Fadli; Ima Astuty Wunawarsih; salahuddin salahuddin (Jurnal Ilmiah Penyuluhan dan Pengembangan Masyarakat, 2021)
This study aims to determine the use of the internet by agricultural instructors to improve the performance of rice agricultural instructors in Angata District, South Konawe Regency. This research was conducted in Angata District in July-August 2021 and used quantitative research methods. The results of this study indicate that the relationship between the use of the internet and the performance improvement of agricultural instructors in Angata sub-district has a significant relationship which is calculated using the Spearman Rank formula. This can be seen from the high use of the internet by agricultural extension workers which is calculated using the interval analysis formula, while the performance of agricultural instructors is in the good category which is calculated based on the Minister of Agriculture of the Republic of Indonesia No. 91 of 2013 concerning Guidelines for Evaluation of Agricultural Extension Performance. Based on the results of the Spearman rank analysis, the elements of internet use consisting of Situation Analysis, Improving Knowledge, Problem Awareness, Decision Making, and Motivation and Skills have a significant relationship with the performance of agricultural instructors in Angata sub-district.